Penerapan Pendampingan Dalam Meningkatkan Kompetensi Supervisi Akademik Kepala SMA Binaan di Wilayah Kabupaten Nias Barat - Gloriantina Laoli (Simpati, 2023)
This research is motivated by the lack of school principals’ competency to carry out academic supervision. This study aims to improve the ability of school principals' academic supervision, especially in planning, implementing, evaluating and following up on academic supervision. The research was conducted in 7 (seven) assisted high schools in West Nias Regency. The research subjects were 7 school principals. The research was conducted using the School Action Research (PTS) method for 2 cycles. Actions taken to improve the supervisory competence of school principals are mentoring activities from school supervisors. The results showed that in cycle I there was an increase in the competency of school principals' academic supervision after mentoring by 57.14%, and in cycle II the ability of school principals increased to 100%. The conclusion from this study is that the assistance provided by school supervisors can improve the competency of school principals to carry out academic supervision. Therefore, it is hoped that school supervisors will always provide assistance to school principals on an ongoing basis, so that it has a positive impact on improving teacher performance and student learning outcomes.